2021
DOI: 10.1016/j.jgo.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Are clinical trial eligibility criteria representative of older patients with lung cancer? A population-based data linkage study

Abstract: Objectives: Older adults constitute the majority of patients with lung cancer. However, they are underrepresented in clinical trials as eligibility criteria often restrict enrolment based on comorbidities that are common with aging. We aimed to describe comorbidities relating to trial exclusion criteria in older adults with lung cancer, determine the proportion that would typically be excluded from trials, and examine the impact on treatment uptake. Materials and Methods: We conducted a population-based study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Lack of applicability of CPGs was seen to result from CPGs not catering for patient complexities, a universal CPG adherence issue [52], as CPGs are often underpinned by evidence from clinical trials comprised of patients who are unrepresentative of real-world populations. Instead, trial cohorts are often restricted to a subset of fitter patients, with lower risk profiles, often excluding patients based on age, organ function and lack of comorbidities [53][54][55]. Patient age [10,11,[56][57][58] and comorbidities [56,[58][59][60][61][62] are factors independently associated with cancer CPG non-adherence.…”
Section: Frequency Analysismentioning
confidence: 99%
“…Lack of applicability of CPGs was seen to result from CPGs not catering for patient complexities, a universal CPG adherence issue [52], as CPGs are often underpinned by evidence from clinical trials comprised of patients who are unrepresentative of real-world populations. Instead, trial cohorts are often restricted to a subset of fitter patients, with lower risk profiles, often excluding patients based on age, organ function and lack of comorbidities [53][54][55]. Patient age [10,11,[56][57][58] and comorbidities [56,[58][59][60][61][62] are factors independently associated with cancer CPG non-adherence.…”
Section: Frequency Analysismentioning
confidence: 99%
“…The PACIFIC study ( 34 ) also demonstrated an improvement in overall survival with the addition of durvalumab after concurrent chemoradiation. Unfortunately, over half of all older adults with advanced lung cancer are excluded from clinical trials ( 35 ). Future directions will hopefully explore GA-guided recommendations in a prospective clinical trial design among older adults with GA impairment receiving chemotherapy + IO for stage IV and chemoradiation therapy for stage III NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…This is higher than the 12% we reported in an older patient cohort (median age 84 years vs. mean age 72 years) over a similar period. 3 Clearly, factors associated with uptake of systemic therapy are of critical interest, as survival outcomes are unlikely to improve if patients do not receive recommended treatment. Ngo et al report that older age, poor performance status (PS), socioeconomic disadvantage, and less educational attainment were associated with lower likelihood of receiving systemic therapy.…”
Section: Timely and Comprehensive Real-world Data For Optimizing Lung...mentioning
confidence: 99%